False memory and COVID-19: How people fall for fake news about COVID-19 in digital contexts - Mangiulli, Ivan; Battista, Fabiana; Kafi, Nadja Abdel; Coveliers, Eline; Webster, Theodore Carlson; Curci, Antonietta; Otgaar, Henry (Frontiers in Psychology, 2022)
People are often exposed to fake news. Such an exposure to misleading information might lead to false memory creation. We examined whether people can form false memories for COVID-19-related fake news. Furthermore, we investigated which individual factors might predict false memory formation for fake news. In two experiments, we provided participants with two pieces of COVID-19-related fake news along with a non-probative photograph. In Experiment 1, 41% (n = 66/161) of our sample reported at least one false memory for COVID-19-related fake news. In Experiment 2, even a higher percentage emerged (54.9%; n = 185/337). Moreover, in Experiment 2, participants with conspiracy beliefs were significantly more likely to report false memories for fake news than those without such beliefs, irrespective of the conspiratorial nature of the materials. Finally, while well-being was found to be positively associated with both true and false memories (Experiment 1), only analytical thinking was negatively linked to the vulnerability to form false memories for COVID-19-related fake news (Experiment 2). Overall, our data demonstrated that false memories can occur following exposure to fake news about COVID-19, and that governmental and social media interventions are needed to increase individuals’ discriminability between true and false COVID-19-related news.